Field Guide to Owls of California and the West. - Peeters, Hans J. (CA : University of California Press, 2007)
Most owls are almost perfectly adapted to life in the dark. Their vaguely humanoid faces reflect the spectacular evolution of their hearing and vision, which has made flight, romance, and predation possible in the near absence of light. This accessible guide, full of intriguing anecdotes, covers all 19 species of owls occurring in North America. More than an identification guide, Field Guide to Owls of California and the West describes the biology and behavior of owls to make finding and identifying them easier and watching them more enjoyable. The guide also explores the conservation challeng.
Eastern Screech-OwlWhiskered Screech-Owl; Great Horned Owl; Snowy Owl; Northern Hawk Owl; Northern Pygmy-Owl; Ferruginous Pygmy-Owl; Elf Owl; Burrowing Owl; Spotted Owl; Barred Owl; Great Gray Owl; Long-eared Owl; Short-eared Owl; Boreal Owl; Northern Saw-whet Owl; Glossary; References; Index; Additional Captions.
Print version record.
Includes bibliographical references (p. 281-303) and index.
English.
JSTOR
Keywords: Owls -- California; Owls -- West (U.S.); NATURE -- Animals -- Birds; NATURE -- Birdwatching Guides; SCIENCE -- Life Sciences -- Zoology -- Ornithology; Owls; California; West United States; american west; barn owl; barred owl; biology; body of an owl; burrowing owl; california natural history guides; california; conservation; evolution; finding owls; flammulated owl; great grey owl; great horned owl; life in the dark; life of an owl; long eared owl; native american culture; natural history; nest boxes; north american owls; northern pygmy owl; northern saw whet owl; northern spotted owl; owl behavior; owls and humans; owls; short eared owl; species; watching owls; western screech owl; zoology